Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1093/hr/uhad004
|View full text |Cite
|
Sign up to set email alerts
|

Jasmonic acid regulates the biosynthesis of medicinal metabolites via the JAZ9-MYB76 complex inSalvia miltiorrhiza

Abstract: Jasmonic acid (JA) signaling pathway plays an important role in tanshinone and phenolic acid biosynthesis in Salvia miltiorrhiza. However, the specific regulatory mechanism remains largely unclear. Previous work showed that a JASMONATE ZIM-domain (JAZ), SmJAZ9, acted as a repressor of tanshinone production in S. miltiorrhiza. In this study, we revealed that SmJAZ9 reduced both phenolic acid accumulation and related biosynthetic gene expression, confirming that SmJAZ9 also negatively affected phenolic acid bios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Moreover, drought stress could also stimulate ABA accumulation. For example, in P. nutans , PYL, PP2C, and SnRK2 were notably upregulated [ 64 ]. DEGs that encode PYL, PP2C, and SnRK2 in our research, however, showed a decrease or no significant change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, drought stress could also stimulate ABA accumulation. For example, in P. nutans , PYL, PP2C, and SnRK2 were notably upregulated [ 64 ]. DEGs that encode PYL, PP2C, and SnRK2 in our research, however, showed a decrease or no significant change.…”
Section: Discussionmentioning
confidence: 99%
“…TFs are crucial for the response to drought stress and the regulation of secondary metabolites [ 64 , 65 ]. Previous results have proven that some TFs function through the MAPK signaling pathway and plant hormone signal transduction.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that SmHDA5 also positively correlated with the expression of SmJAZ9 . In previous reports, SmJAZ9 was shown that it can form the complex with SmMYB76 , further inhibit the expression of the synthetic gene SmRAS1 , SmMYB76 was also associated with SmHDA5 [ 2 ]. The addition of SmHDA5 may provide a new idea for the molecular mechanism of SmMYB76 inhibiting salvianolic acid synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Salvia miltiorrhiza is a Chinese traditional medicinal plant that has been used for thousands of years. It is rich in water-soluble component salvianolic acids and lipid-soluble component tanshinones [ 1 , 2 ], which is used to combat the increasing incidence of cardiovascular disease [ 3 , 4 ]. However, the wild resources of S. miltiorrhiza are decreasing continuously, which cannot meet the market demand.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation